In situ genetic engineering of tumors for long-lasting and systemic immunotherapy - Tzeng, Stephany Y.; Patel, Kisha K.; Wilson, David R.; Meyer, Randall A.; Rhodes, Kelly R.; Green, Jordan J. (Proceedings of the National Academy of Sciences - PNAS, 2020)
Cancer immunotherapy has been the subject of extensive research, but highly effective and broadly applicable methods remain elusive. Moreover, a general approach to engender endogenous patientspecific cellular therapy, without the need for a priori knowledge of tumor antigen, ex vivo cellular manipulation, or cellular manufacture, could dramatically reduce costs and broaden accessibility. Here, we describe a biotechnology based on synthetic, biodegradable nanoparticles that can genetically reprogram cancer cells and their microenvironment in situ so that the cancer cells can act as tumor-associated antigen-presenting cells (tAPCs) by inducing coexpression of a costimulatory molecule (4-1BBL) and immunostimulatory cytokine (IL-12). In B16-F10 melanoma and MC38 colorectal carcinoma mouse models, reprogramming nanoparticles in combination with checkpoint blockade significantly reduced tumor growth over time and, in some cases, cleared the tumor, leading to long-term survivors that were then resistant to the formation of new tumors upon rechallenge at a distant site. In vitro and in vivo analyses confirmed that locally delivered tAPC-reprogramming nanoparticles led to a significant cell-mediated cytotoxic immune response with systemic effects. The systemic tumor-specific and cell-mediated immunotherapy response was achieved without requiring a priori knowledge of tumor-expressed antigens and reflects the translational potential of this nanomedicine.